Abnormal synaptic Ca2+ homeostasis and morphology in cortical neurons of familial hemiplegic migraine type 1 mutant mice. Issue 2 (6th July 2015) - Eikermann‐Haerter, Katharina; Arbel‐Ornath, Michal; Yalcin, Nilufer; Yu, Esther S.; Kuchibhotla, Kishore V.; Yuzawa, Izumi; Hudry, Eloise; Willard, Carli R.; Climov, Mihail; Keles, Fatmagul; Belcher, Arianna M.; Sengul, Buse; et al.
<x xml:space="preserve">Abstract</x> Objective Migraine is among the most common and debilitating neurological conditions. Familial hemiplegic migraine type 1 (FHM1), a monogenic migraine subtype, is caused by gain‐of‐function of voltage‐gated CaV2.1 calcium channels. FHM1 mice carry human pathogenic mutations in the α1A subunit of CaV2.1 channels and are highly susceptible to cortical spreading depression (CSD), the electrophysiologic event underlying migraine aura. To date, however, the mechanism underlying increased CSD/migraine susceptibility remains unclear. Methods We employed in vivo multiphoton microscopy of the genetically encoded Ca2+‐indicator yellow cameleon to investigate synaptic morphology and [Ca2+]i in FHM1 mice. To study CSD‐induced cerebral oligemia, we used in vivo laser speckle flowmetry and multimodal imaging. With electrophysiologic recordings, we investigated the effect of the CaV2.1 gating modifier tert‐butyl dihydroquinone on CSD in vivo. Results FHM1 mutations elevate neuronal [Ca2+]i and alter synaptic morphology as a mechanism for enhanced CSD susceptibility that we were able to normalize with a CaV2.1 gating modifier in hyperexcitable FHM1 mice. At the synaptic level, axonal boutons were larger, and dendritic spines were predominantly of the mushroom type, which both provide a structural correlate for enhanced neuronal excitability. Resting neuronal [Ca2+]i was elevated in FHM1, with loss of compartmentalization between synapses and neuronal shafts. The percentage of calcium‐overloaded neurons was increased. Neuronal [Ca2+]i surge during CSD was faster and larger, and post‐CSD oligemia and hemoglobin desaturation were more severe in FHM1 brains. Interpretation Our findings provide a mechanism for enhanced CSD susceptibility in hemiplegic migraine. Abnormal synaptic Ca2+ homeostasis and morphology may contribute to chronic neurodegenerative changes as well as enhanced vulnerability to ischemia in migraineurs. Ann Neurol 2015;78:193–210